Spiral : trapped in the forever war - Danner, Mark, 1958- (Simon & Schuster, 2016)
"Trapped in a forever war by 9/11, in Spiral Mark Danner describes a nation that has been altered in fundamental ways. President Bush declared a war of choice and without an exit plan, and President Obama has proven unable to take the country off what he has called its "permanent war footing." The War on Terror has led to fourteen years of armed conflict, the longest war in America's history. Al Qaeda, the organization that attacked us on 9/11, has been "decimated" (the word is Obama's) but replaced by multiple jihadist and terror organizations, including the most notorious--ISIS. Spiral is what we can call a perpetual and continuously widening war that has put the country in a "state of exception." Bush's promise that we have "taken the gloves off" and Obama's inability to define an end game have had a profound effect on us even though the actual combat is fought by a tiny percentage of our citizens. In the name of security, some of our accustomed rights and freedoms are circumscribed. Guantanamo, indefinite detention, drone warfare, enhanced interrogation, torture, and warrantless wiretapping are all words that have become familiar and tolerated. And yet the war goes badly as the Middle East drowns in civil wars and the Caliphate expands and brutalized populations flee and seek asylum in Europe. In defining the War on Terror as boundless, apocalyptic, and unceasing, we have, Danner concludes, "let it define us as ideological crusaders caught in an endless war.""--